Evaluation of skin procurement and storage techniques for Tissue Banking - Calvo-Castro, Laura A. (2015)
Here we report how we reproduced and analyzed the most common international techniques for managing skin for Tissue Banking. Skin ablation, processing, disinfection and storage were performed using an animal model (domestic pig, Sus scrofa domesticus). Two different disinfection methods were compared (antibiotics and chemical disinfection with chlorine) by evaluating the microbiology profile of the tissue. Also, two different storage and preservation treatments were compared: glycerol immersion at low temperatures (4°C) and cryopreservation (-70°C). Finally, we analyzed the sterilization of the tissue by electron beam irradiation (25 kGy). General structural changes in the tissue were analyzed by histological staining. Our results show that complete sterilization of the samples was achieved in both the irradiated tissue and in the chemically disinfected glycerolated skin (Dakins solution). Histological comparison between treatments revealed that samples kept in glycerol showed the best structural quality.